Pengaruh Desain Produk, Kualitas Produk, Citra Merek, Harga Terhadap Kepuasan Konsumen Susu Dancow Di Kota Medan - Meysi Ramayana Munthe; Fajrillah Fajrillah; Ripka SeriIdahnaita Ginting (LPPM Politeknik LP3I Medan, 2021)
This study aims to examine the effects of product design, product quality, brand image and price on consumer satisfaction with dancow milk product in Medan city. This study used quantitative descriptive method and the sample used is100 consumer who consume dancow milk product in Medan city. The analysis method used is multiple linier regression. The results of data analysis show that partially and simultaneously the product design, product quality, brand image and price shows a positive coefficient number and has a significant effect on consumer satisfaction. The coefficient determination of 0,481 means that the variable product design, product quality, brand image and price has explain the effect on consumer satisfaction by 48,1% while the remaining 51,9 % is another independent vatriable not examined in this study.